Design and Build a Multilevel Mace Nutmeg Dryer to Improve the People's Economy - Ihsan, Ihsan; Ilham, Dirja Nur; Putra, Reza Ade; Candra, Rudi Arif; Budiansyah, Arie (Politeknik Ganesha Medan, 2021)
Nutmeg is a source of income for some people in South Aceh, and some types of nutmeg, like mace nutmeg, are of better quality. Mace nutmeg is also an agricultural community with great economic value and benefits for humans, as it can be processed into spices and herbs. A range of products includes nutmeg oil and medicines. The harvesting and drying of mace nutmeg, which is still considered a problem by nutmeg growers, cannot be isolated from the processing of the basic ingredients. The natural process of drying mace nutmeg involves the use of sunshine, which necessitates a considerable drying time. Therefore nutmeg farmers frequently complain of erratic weather, especially during the wet season. The constant rain can cause the mace to rot, causing the nutmeg farming community's revenue to become unstable. Methods and steps of research work starting from the study of literature, determination of design specifications, hardware design, software design, toolmaking, tool testing.Good results were reached with the dryness of the mace nutmeg, which can be adjusted, and without putting into account the weather in the drying process, which is usually done with the heat of the sun, per the results of the testing of the designed tools.The average dryness of mace nutmeg is at a temperature of 45 percent with a time of 4 hours and a capacity of 100 grams; according to the test results of the automatic mace drying machine, it produces 50 grams of dry mace.